2015
DOI: 10.4236/ojpm.2015.53013
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Medical Absenteeism among Secondary School Students: An Observational Study on Their Health Condition from a Biopsychosocial Perspective

Abstract: An adequate approach to reducing school absenteeism should focus on medical absenteeism as this is the most prevalent form of school absenteeism. The objective of this study is to explore the health condition of pre-vocational secondary students with extensive medical absenteeism from a biopsychosocial perspective. Data were obtained from medical assessments and Strengths and Difficulties Questionnaires (SDQs) of students with medical absence above threshold criteria (i.e. reported sick four times in 12 school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Furthermore, both students who report one to four sick days in the past eight weeks and students with more than four sick days in the past eight weeks showed decreased physical HRQOL. This is in accordance with research that found a link between physical conditions and school absenteeism [6,23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, both students who report one to four sick days in the past eight weeks and students with more than four sick days in the past eight weeks showed decreased physical HRQOL. This is in accordance with research that found a link between physical conditions and school absenteeism [6,23].…”
Section: Discussionsupporting
confidence: 93%
“…On the short term, school absenteeism due to health issues or truancy is associated with lower educational performance, physical complaints and psychosocial problems [3,19,20,21,22,23]. A main long-term consequence is early school leaving [6,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This can result in a raised threshold for reporting sick in future because students cannot avoid attention. The decrease in medical absenteeism can also be attributed to the intervention of the YHCP, resulting in more personalised and adequate treatment, care or support: after analysing the great variability of underlying reasons for the absenteeism [ 43 ], appropriate care, educational adjustments and adequate support could be arranged by schools and YHCPs in a sustainable manner. As a consequence, students possibly experience fewer (health-related) problems and/or find better ways to deal with their problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, the follow-up is experienced as difficult. When teachers themselves discuss the absence with students and parents initially, it makes it easier to follow-up of the feedback because, from the start, teachers are more actively involved Moreover, as shown in our study on students’ health condition [ 29 ], extensive medical absenteeism may also be caused by problems in school. This is an additional reason to have a dialogue by school before referring to the YHCP.…”
Section: Discussionmentioning
confidence: 99%